Analisis Perhitungan Kebutuhan Tenaga Kesehatan Perawat dengan Metode Workload Indicator Staff Need (WISN) - Minati, Tengku Nanda Edwina; Girsang, Ermi; Ramadhani, Sri Lestari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The balance between the number of nursing staff and workload is crucial to ensure the quality of healthcare services. A mismatch between staffing levels and workload can lead to fatigue, decreased performance, and reduced quality of care. This study aims to analyze the calculation of nursing staff requirements using the Workload Indicator of Staffing Need (WISN) method in the inpatient units of Mitra Guray Petumbukan General Hospital. The specific objectives are to determine the available working time, existing human resource categories, workload standards, allowance standards, and the number of nurses required based on actual workload. This research employs a quantitative descriptive method with an observational approach, involving 20 nurses as the sample. Data were collected through observation, interviews, and document review of nursing activities, and analyzed using the WISN components, namely available working time, workload standards, and allowance factors. The results showed that the available working time was 3,132 hours per year, with an average of 9 nurses on the morning shift and 6 nurses on the night shift. The total staffing requirement based on the WISN calculation was 22.1 nurses, while the actual number of nurses was 20, resulting in a WISN ratio of 0.9, indicating a shortage of two nurses. The study concludes that the number of nurses in the inpatient units of Mitra Guray Petumbukan General Hospital is not yet fully balanced with the existing workload. It is recommended that the hospital add more nursing staff, organize work schedules more proportionally, and regularly evaluate workload to maintain the quality of nursing services.